Internal Control Systems, Working Capital Management and Financial Performance of Private Institutions in Uganda: An Empirical Study in Mbarara District - Eton, Marus; Fabian, Mwosi; Siraje, Kaaya; Benard, Patrick Ogwel; Edward, Ahabwe (International Journal of Research in Engineering, IT and Social Sciences, 2020)
This research adopted a cross-sectional and descriptive design. Data was collected using self administered questionnaire from those operating businesses in Mbarara municipality. Data was analyzed using a multivariate analysis technique and presented descriptively using mean, standard deviation and coefficient of variation. The study revealed that the businesses were weak at aligning their operations with set business procedures, guidelines and national laws The study also established that the current level of internal control systems is moderately effective. These are commendable practices especially in small and medium enterprise businesses. The moderate relationship between internal control systems and working management confirms the likelihood that these businesses conduct regular financial audits and endeavor to maintain reliable financial records. The study recommended that there is need for businesses to align their operations to national standards and also train their staff in internal control activities that ensure adherence to principles of accounting and financial records. Government has a role to play in protecting nationals against consumption of goods and services that do not measure to national or international standards